Homologous acetylenic acetogenins from Porcelia macrocarpa R.E. (Fries) displayed potent activity against amastigotes from Trypanosoma cruzi - Brito, Ivanildo A.; Castro Levatti, Erica V.; Regasini, Luis O. [UNESP]; Ferreira, Edgard A.; Lopes, Flavia B.; Fernandes, João Paulo S.; Batista, João M.; Tempone, Andre G.; Lago, João Henrique G. (Elsevier, 2025)
As part of our continuous study on the Annonaceae species Porcelia macrocarpa, in the present work, eight chemically related 2-alkyl-3-hydroxy-4-methyl-γ-lactones (1–8) were isolated. Their structures were characterised by NMR, MS, and VCD. Their antitrypanosomal activity was evaluated in vitro against intracellular amastigotes with EC50 values ranged from 13.9 to 1.1 μM for compounds 1–3 and 6–8, while compounds 4 and 5 were inactive (EC50 > 100 μM). Compounds 1–8 did not exert toxicity against NCTC cells at the highest tested concentration (CC50 > 200 μM). Compared with the standard drug benznidazole (EC50 = 3.6 μM and SI > 54.6), compound 8 proved to be the most potent γ-lactone with an EC50 of 1.1 μM and an SI of >181.8. Finally, the structure–activity relationship analysis suggested that flexibility and length of side chain of the related γ-lactones 1–8 play an important role in the activity against amastigotes. The results contribute to the discovery of new molecular prototypes that can be used as scaffolds for developing drugs to treat Chagas disease.
Keywords: Acetogenins; Annonaceae; Chagas disease; Porcelia macrocarpa; SAR; Trypanosoma cruzi